Aerosol Optical Depth variations due to local breeze circulation in Kongsfjorden, Spitsbergen - Malgorzata Cisek; Tomasz Petelski; Tymon Zielinski; Przemyslaw Makuch; Paulina Pakszys; Anna Rozwadowska; Piotr Markuszewski (Oceanologia, 2017)
This paper presents the results of Aerosol Optical Depth (AOD) studies which took place in Ny-Ålesund in the spring of 2014 during the iAREA campaign. The measurements were taken using Microtops II hand-held sunphotometers along the Kongsfjorden, on a path leading from the research village to the fjord opening. Local breeze circulation was observed during the measurement campaign which resulted in an evident increase of AOD along the measurement profile towards the open sea. Using the observed AOD, changes over the open sea have been calculated and the location of the breeze front has been determined.